2014
DOI: 10.1111/den.12396
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the thread‐traction method in esophageal endoscopic submucosal dissection: Randomized controlled trial

Abstract: The TT method in esophageal ESD was safe and contributed to shortening of dissection time. The TT method is expected to become widespread as a safe and useful procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 20 publications
0
56
0
1
Order By: Relevance
“…Upon pulling of the suture externally, countertraction could be achieved for better exposure of the submucosal plane. A shorter duration of procedure using the "clip traction" method was required compared to conventional ESD (33). Careful hemostasis is needed to avoid reactionary and delayed hemorrhage.…”
Section: Endoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%
“…Upon pulling of the suture externally, countertraction could be achieved for better exposure of the submucosal plane. A shorter duration of procedure using the "clip traction" method was required compared to conventional ESD (33). Careful hemostasis is needed to avoid reactionary and delayed hemorrhage.…”
Section: Endoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%
“…This TTSPS made it possible to pull the lesion toward the anal as well as the oral side in gastric cancers [16, 17], and Yamasaki et al [18, 19] and Yamada et al [20] reported methods for colorectal cancers. As a randomized prospective study, Koike et al reported that the thread-traction method was safe and shortened the dissection time and concluded that the thread-traction method was a safer and more useful procedure for esophageal cancers [2123]. The main conclusions of these studies were that creating good working space for ESD between muscular propria and resected lesion reduced adverse event such as perforation and bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the efficacy of the Thread-Traction method (T-T method) with clips was reported for esophageal ESD, and this procedure has become widespread in Japan 29 30 31. Since the T-T method with clips tenses the submucosal tissue in front of the endoscope, we used this method to transmit the power of the waterjet directly to the edge of dissection and successfully completed the procedure.…”
Section: Discussionmentioning
confidence: 99%